M. PUENTE - Pabellones de Exposición - Jerez Abajo, Enrique (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Moisés PuentePabellones de Exposición / Pavilhões de ExposiçãoBarcelona: Gustavo Gili, 2000, 192 pages. Languages: Spanish, Portuguese.ISBN: 84-252-1817-9